Blurred Boundaries: Maintaining Work-Life Balance in the Gig Economy - Achmad Syarifudin (Talenta Publisher, 2024)
The gig economy is a result of the digital developments occurring globally. With its high level of flexibility, the gig economy has transformed the landscape of modern work. However, behind the ease and flexibility, new challenges arise concerning work-life balance. This study analyzes how the boundaries between work and personal life have become increasingly blurred for gig workers. The research method used is a literature review method. A literature review is a research method that involves collecting, analyzing, and synthesizing information from various relevant sources, such as scientific journals, books, articles, research reports, and other sources. Through literature reviews and case studies, this research identifies factors contributing to the work-life imbalance, such as high performance demands, constant accessibility, and the lack of social protection. The study concludes that a collective effort is needed from various parties, including platforms, governments, and gig workers themselves, to create a healthier and more sustainable work environment. Keyword: Gig Economy, work-Life Balance